Protective Effects of At1-Receptor Blocker and Ca Antagonist Combination on Renal Function in Salt Loaded Spontaneously Hypertensive Rats/ Протективни Ефекти На Комбинацијата На Ат1 Рецепторен Блокатор И Калциум Антагонист Врз Реналната Функција Кај Спонтано Хипертензивни Стаорци Оптоварени Со Сол - Gjorgjievska, Kalina; Zafirov, Dimche; Jurhar Pavlova, Maja; Cekovska, Svetlana; Atanasovska, Emilija; Pavlovska, Kristina; Zendelovska, Dragica (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2015)
Salt sensitive hypertension is known to be a contributing factor for the progression of kidney disease. This study was undertaken to investigate the role of excessive dietary salt on renal function and to evaluate the effect of valsartan and amlodipin given as a combination therapy on blood pressure and parameters specific to the renal function in salt loaded SHR rats. 48 male SHR rats at age of 20 weeks and body weight ranging between 270-350 g were used. SHR rats were divided into 3 groups: control group of rats -SHRC (n = 16) given tab water ad libitum and two salt treated groups in which tab water was replaced with a solution of NaCl (1%) from age of 8 weeks given ad libitum: SHRVAL+AMLO group (n = 16) where investigated drugs were administered at a dose of 10 mg/kg/ b.w. (valsartan) and 5 mg/kg/ b.w. (amlodipin) by gavage and SHR NaCl group (n = 16) that received saline in the same volume and the same time intervals as the SHRVAL+AMLO group. For a period of 12 weeks we have investigated the effect of the VAL+AMLO drug combination on systolic blood pressure (SBP), body weight and renal function tests. Salt loading with 1% solution in the SHR NaCl group has lead to significant increase of blood pressure, proteinuria and decrease in creatinine clearance. Combined treatment with АТ1-receptor blocker and calcium antagonist has managed to control blood pressure and ameliorated renal damage.